2012
DOI: 10.1111/j.1468-1331.2012.03825.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin versus anticoagulation in intra‐ and extracranial vertebral artery dissection

Abstract: Although this was a non-randomized study, our data suggest that the frequency of recurrent ischaemic stroke in patients with intra- or extracranial VAD is low and most likely independent of the type of antithrombotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…In a series of 195 patients with vertebral artery dissections who were recruited in neurology departments in France and Switzerland, only 11% of dissections were located exclusively in the intracranial portion of the artery. 17 In a Mexican study 18 of 100 patients admitted to a neurology department for vertebral artery dissection with ischaemic stroke and without subarachnoid haemor rhage, 27 (27%) patients had intracranial artery dissection. In studies undertaken in east Asia, [19][20][21][22][23] in which patients were mostly recruited through neuro surgery and interventional neuroradiology departments, intracranial artery dissection Review accounted for up to 67-78% of all cervicocephalic artery dissections.…”
Section: Epidemiologymentioning
confidence: 99%
“…In a series of 195 patients with vertebral artery dissections who were recruited in neurology departments in France and Switzerland, only 11% of dissections were located exclusively in the intracranial portion of the artery. 17 In a Mexican study 18 of 100 patients admitted to a neurology department for vertebral artery dissection with ischaemic stroke and without subarachnoid haemor rhage, 27 (27%) patients had intracranial artery dissection. In studies undertaken in east Asia, [19][20][21][22][23] in which patients were mostly recruited through neuro surgery and interventional neuroradiology departments, intracranial artery dissection Review accounted for up to 67-78% of all cervicocephalic artery dissections.…”
Section: Epidemiologymentioning
confidence: 99%
“…The results of the meta-analysis and a recent observational results in cervical artery dissection cases have demonstrated that there is no superiority of anticoagulation over aspirin in the odds of death or the occurrence of ischemic stroke [64,65]. In our cases, we applied antiplatelet therapy, no patients had a hemorrhagic complication, and all patients did well on the mRS during a 3-month follow-up period.…”
Section: Discussionmentioning
confidence: 95%
“…Generally, patients are initially treated with heparin, followed by warfarin or antiplatelet therapy alone (aspirin or aspirin and clopidogrel) (6,8). A study by Arauz et al compared treatment with oral anticoagulation versus aspirin alone and found that the incidence of recurrent ischemic stroke in patients with a vertebral artery dissection is low and likely independent of the type of antithrombotic treatment (9). However, how early the diagnosis is made and the severity of the sequelae may determine the best mode of therapy.…”
Section: Discussionmentioning
confidence: 99%